2019
DOI: 10.1111/dmcn.14412
|View full text |Cite
|
Sign up to set email alerts
|

Sitting in patients with spinal muscular atrophy type 1 treated with nusinersen

Abstract: Aim To determine factors associated with acquisition of a sitting position in patients with spinal muscular atrophy type 1 (SMA1) treated with nusinersen. Method Using data from the registry of patients with SMA1 treated with nusinersen, we compared the subgroups of sitters and non‐sitters after 14 months of therapy as a function of baseline level, SMN2 copy number, age at treatment initiation, and improvement at 2 and 6 months post‐treatment initiation. We used Hammersmith Infant Neurological Examination, Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 20 publications
0
43
0
1
Order By: Relevance
“…This improvement is exceptional in symptomatic children with SMA type 1 and may be misleading both for some parents of much more affected children, and for clinicians who are not deeply involved in this field of research. For treatment with Nusinersen Aragon-Gawinska et al have shown that higher baseline motor function is associated with higher probability of acquisition of motor milestones [13]. At the other end of the spectrum, more severely affected patients, who do already depend on respiratory support and tube feeding at initiation of treatment, do in most cases only demonstrate very modest improvement if at all [14e16].…”
Section: Strength Of Consensus: Strong Consensus (100%)mentioning
confidence: 99%
“…This improvement is exceptional in symptomatic children with SMA type 1 and may be misleading both for some parents of much more affected children, and for clinicians who are not deeply involved in this field of research. For treatment with Nusinersen Aragon-Gawinska et al have shown that higher baseline motor function is associated with higher probability of acquisition of motor milestones [13]. At the other end of the spectrum, more severely affected patients, who do already depend on respiratory support and tube feeding at initiation of treatment, do in most cases only demonstrate very modest improvement if at all [14e16].…”
Section: Strength Of Consensus: Strong Consensus (100%)mentioning
confidence: 99%
“…The effectiveness of treatment observed in randomized drug trials is confirmed by the results of open clinical trials and real-world data. [12][13][14][15][16][17] In drug trials, 323 patients with various forms of SMA (SMA1, 2, 3 and presymptomatic) were treated with nusinersen. Currently, over 11,000 patients worldwide receive the drug (October 2020).…”
Section: Sma Therapymentioning
confidence: 99%
“…Real-world data indicate that up to 30% of symptomatically treated SMA1 patients (15/47 in the group treated for 14 msc, aged 2.5-102.8 msc and 2/61 and 3/16 treated for 6 msc) achieved sitting ability. 15,16,24 Thus, the ability to achieve independent sitting in children with SMA1 treated symptomatically with nusinersen might be estimated at 30-50%, depending on the age of treatment initiation. This efficacy of symptomatic treatment is incomparably lower than the results of presymptomatic treatment.…”
Section: Nusinersen (Spinraza)mentioning
confidence: 99%
“…Dziecko musi być badane najlepiej rano, kiedy jest ożywione. Dozwolone są trzy próby wykonywania danej czynności [2,10].…”
Section: Metody Oceniające Motorykę Dużą I Małą U Pacjentów Z Sma Typuunclassified